2017
DOI: 10.1007/s00384-016-2745-9
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell dysplasia in the proximal rectum of three patients treated for ulcerative colitis on immunomodulators

Abstract: This study highlights the potential for HSIL to extend into the rectum either as a contiguous patch or isolated islands and the need for heightened surveillance in patients with extensive anal canal HSIL treated with immunodulator therapy. HSIL identified at the limit of the anoscope should be investigated further with colonoscopy, and argon plasma coagulation (APC) ablation can serve as an effective treatment option. Patients are at risk for stricture, but it is unclear what role the UC or the ablation played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Corticosteroids are used for short-term treatment and cannot bene t from long-term use because of the many complications associated with long-term use, such as osteoporosis and hypertension [23,24]. Long-term use of immunomodulators is not only toxic, but one case follow-up showed possible transformation into high-grade squamous intraepithelial lesions, which are precancerous [25]. Biologics such as anti-TNF drugs not only increase the risk of infection in UC patients, but may also present with various types of TB [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are used for short-term treatment and cannot bene t from long-term use because of the many complications associated with long-term use, such as osteoporosis and hypertension [23,24]. Long-term use of immunomodulators is not only toxic, but one case follow-up showed possible transformation into high-grade squamous intraepithelial lesions, which are precancerous [25]. Biologics such as anti-TNF drugs not only increase the risk of infection in UC patients, but may also present with various types of TB [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids, treated for short-term therapeutic interventions, are beset by a multitude of complications upon extended usage, encompassing osteoporosis and hypertension [ 22 , 23 ]. Previous case report revealed that, despite their therapeutic potential, the prolonged treatment of immunomodulatory agents might lead to the precancerous lesions such as high-grade squamous intraepithelial lesions [ 24 ]. While anti-TNF can be used for severe ulcerative colitis treatment, there’s a risk of recurrence if it is discontinued [ 25 ].…”
Section: Discussionmentioning
confidence: 99%